Clinical case of fulminant hepatitis in a child with hepatolenticular degeneration - I.M. Nesina; T.O. Kryuchko; O.A. Poda; L.A. Kovalenko; M.O. Pavlenko (Zaslavsky O.Yu., 2021)
The article presents a detailed analysis of the diagnostic search for Wilson's disease in childhood. Polymorphism of clinical symptoms of the disease has led to various descriptions of this pathology and its manifestations. Despite more than a century of experience in studying the peculiarities of hepatolenticular degeneration, at the present stage the diagnosis of the disease, especially in children, remains a difficult issue. According to the literature data, there are no characteristic symptoms and typical clinical picture of this disease, which is the reason for the late diagnosis of this pathology in children. The earlier treatment is started, especially if at the preclinical stage, the higher is the efficacy and the more favorable the prognosis will be observed. The article summarizes information about the objective difficulties of proper diagnosis of this disease. In a specific clinical case presented in the article, the onset of hepatolenticular degeneration arose in the form of fulminant hepatitis with the development of acute liver failure, in which cytolysis of hepatocytes led to the release of copper that increased the content of the microelement in the blood. Particular attention should be paid to the symptoms that should alert the practitioner to Wilson's disease, exactly such as the presence of jaundice of unknown origin, bleeding gums or multiple ecchymoses on the skin of the chest and back, a specific type of stripes (white, periodically changing color to reddish-blue) on thighs and axillary areas; hormonal disorders in the form of amenorrhea or dysmenorrhea in girls, as well as decreased intelligence and mental changes in the form of mood swings, or attacks of aggression, problems with school performance. Particular attention is paid to the role of an edema-ascites syndrome, in the absence of signs of portal hypertension, which is a pathognomonic sign of the onset of abdominal hepatolenticular degeneration, which is associated with early liver dysfunction.